2023
DOI: 10.1002/jhet.4617
|View full text |Cite
|
Sign up to set email alerts
|

Chalcones: Versatile intermediates in heterocyclic synthesis

Abstract: Chalcones are a fascinating and well‐studied group of organic molecules. Synthesis of chalcones has been one of the essential areas of organic synthesis over the last few decades because of their immense therapeutic and excellent photophysical properties. Furthermore, these chalcone derivatives can be utilized to make a variety of heterocyclic compounds, especially five‐ and six‐membered heterocycles. Heterocyclic compounds have a long history in chemistry, primarily in pharmaceuticals. However, synthesizing s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 175 publications
(176 reference statements)
0
9
0
Order By: Relevance
“…This journal is © The Royal Society of Chemistry 2023 4.2.1.6.2.Aza-Michael addition of hydrazine derivatives and hydroxylamine to chalcones Many biologically active pyrazoles and isoxazoles have been generated by the interaction of chalcones with hydrazine derivatives or hydroxyl amines. 129,130 The usage of pyrazoles as antioxidants in fuels, anesthetics, and agricultural uses, as well as in pharmaceuticals and dyes, 131 has attracted attention from researchers. [132][133][134] These substances are helpful for materials chemistry, brightening, and electroluminescence.…”
Section: Organic and Biomolecular Chemistry Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…This journal is © The Royal Society of Chemistry 2023 4.2.1.6.2.Aza-Michael addition of hydrazine derivatives and hydroxylamine to chalcones Many biologically active pyrazoles and isoxazoles have been generated by the interaction of chalcones with hydrazine derivatives or hydroxyl amines. 129,130 The usage of pyrazoles as antioxidants in fuels, anesthetics, and agricultural uses, as well as in pharmaceuticals and dyes, 131 has attracted attention from researchers. [132][133][134] These substances are helpful for materials chemistry, brightening, and electroluminescence.…”
Section: Organic and Biomolecular Chemistry Reviewmentioning
confidence: 99%
“…The biological uses of triazole derivatives include as anticonvulsants, antimicrobials, antivirals, antituberculars, antidiabetics, anti-inflammatories, antiproliferatives, antioxidants, anti-ureases, and antimalarials. 129,166 Triazoles are produced when the chalcone undergoes a [3 + 2] cycloaddition reaction with azide molecules. 167,168 Moreover, it was reported that the [3 + 2] cycloaddition reaction of chalcone 123 with 5-azido-5deoxy-1,2-O-isopropylidene-α-D-xylofuranose 124 using tetrabutylammonium hydrogen sulfate (TBAHS) as a catalyst yielded triazole 125, as shown in Scheme 41.…”
Section: Organic and Biomolecular Chemistry Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“… 6 Additionally, owing to their facile synthetic accessibility and ɑ,β-unsaturated carbonyl conjugated system containing two electrophilic centers, they are frequently used as valuable intermediates for the formation of heterocycles, particularly five- and six-membered heterocyclic molecules. 7 Considering the importance of spirooxindoles, fluorine compounds, and chalcones, we hypothesized that their integration could augment the bioactivities. However, to date, there have been few successful examples employing the chalcone-type compounds as the dipolarophiles for the diastereoselective 1,3-dipolar [3 + 2] cycloaddition involving the ketimines 1 ( Scheme 1b ).…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Commonly referred to as chalcones, a-b unsaturated ketones are a signicant family of natural products as well as synthetic chemicals that have shown a variety of biological activity. 6,7 However, not many ways for derivatizing avonoids, particularly chalcones, under Suzuki cross-coupling conditions have been reported. [8][9][10] As parent heterocycles of several commercially available medications, pyrazoline and pyrazole heterocycles have unique biological properties.…”
Section: Introductionmentioning
confidence: 99%